Scientific and methodological approaches to the classification of land affected by military actions in Ukraine - Dorosh, Y; Tarnopolskyi, A.; Dorosh, O.; Kharytonenko, R.; Melnyk, D. (Land Management, Cadastre and Land Monitoring, 2025)
Abstract. The focus is placed on the necessity of classifying lands and land parcels affected by military actions in Ukraine and establishing restrictions on their use. The study identifies the fragmented nature of legal regulation and the absence of a comprehensive approach to determining the legal regime of lands impacted by warfare. A synthesis of scientific literature on land classification has served as the foundation for developing the theoretical framework of a classifier for war-affected lands. The historical experience of managing war-affected lands is analyzed through the examples of the French Republic and the Federal Republic of Germany, which rely on scientific approaches to classifying damaged territories and guiding their recovery. The importance of establishing a classification system for lands affected by military actions is emphasized as a critical component in designing effective strategies for their rehabilitation. A classification system for war-affected lands is proposed, comprising five main categories: physically disturbed lands, littered lands, contaminated lands, mined lands, and lands with mixed contamination and debris. A detailed structure of the classifier is presented, describing the types and subtypes of affected lands, classification levels based on damage severity, the complexity of reclamation, and restrictions on future land use. The proposed classifier structure takes into account all relevant criteria and contributes to the development of effective measures for land restoration. Key words: classification of damaged lands, war-damaged land classifier, military actions, land resources, land reclamation, contaminated lands, mined areas, land use restrictions, littered lands, land restoration, post-war recovery, land condition assessment, land resource management.